Wounded Bodies and Lost Voices in Hemingway’s War Stories of Italy - Tucan Gabriela (Romanian Journal of English Studies, 2018)
This article dwells on three of Hemingway’s canonical short stories, set in Italy. While not entirely autobiographical, they deal with Hemingway’s inner turmoil caused by his experience during World War I. From its inarticulate nature, pain half emerges into conversations between patients and physicians in A Very Short Story and In Another Country, but disappears into silence in A Way You’ll Never Be. The paper argues that the nature of physical and mental wounds, whether visible or concealed, fails objectification.